PHYSICO-CHEMICAL CHARACTERISTICS OF UNTREATED EFFLUENT FROM TANNERY INDUSTRIES IN TAMIL NADU: A COMPARATIVE STUDY - P.SIVAKUMAR; M. KANAGAPPAN; S. SAM MANOHAR DAS (International Journal of Pharma and Bio Sciences, 2015)
The Physico-chemical characteristics of tannery effluents from four different stations, Ambur(latitude of 12.78oN and the longitude of 78.7oE); Vaniyambadi (78o-35o and 78o–38o North latitude and 12o–42o East longitude); Dindigul (latitude of 10.350N and the longitude of 77.950E ); Ranipet (latitude of 12.9420N and the longitude of 79.3230E ) were compared. In stations other than I and III the effluents were alkaline. In station I, the TDS, BOD and COD were comparatively higher. The effluent collected from station I differed significantly from the effluent collected from other stations with reference to the different physico-chemical characteristics based on Tukey Comparision.